Towards More Sustainable Food Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Food systems are under increasing pressure. They must meet the food requirements of a growing world population, and socio-economic changes also influence the type of foods which are under demand. At the same time, food systems are a major contributor to global environmental change, and environmental changes adversely impact agricultural productivity. This Special Issue explores opportunities and challenges towards achieving more sustainable food systems. Essential changes required in food systems are highlighted, such as more effective food distribution, the avoidance or valorisation of food waste, and less meat consumption. How to actually achieve these required changes across food value chains is also presented. This Special Issue supports solution-oriented approaches towards addressing one of most complex challenges of this century. The reader is invited to study the publications included in this Special Issue in detail.